2022
DOI: 10.3390/su14053106
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment and Prediction of Air Pollution Disasters in Four Chinese Regions

Abstract: Evaluating the regional trends of air pollution disaster risk in areas of heavy industry and economically developed cities is vital for regional sustainable development. Until now, previous studies have mainly adopted a traditional weighted comprehensive evaluation method to analyze the air pollution disaster risk. This research has integrated principal component analysis (PCA), a genetic algorithm (GA) and a backpropagation (BP) neural network to evaluate the regional disaster risk. Hazard risk, hazard-laden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…It is interesting to discover that routine physical examination is the primary determinant for household vulnerability to poverty in both urban and rural areas. Even in urban areas, more than 50% of households do not take a physical check-up on time, and empirical studies revealed that the early stages of several critical illness such as Hepaticsclerosis and cardiovascular disease are detected upon physical examination [80][81][82]. The deprivation of routine physical health examinations gives elders the risk of their minor ailments changing to major diseases, which can also offer a reasonable explanation as to why bad health is a key determinant that pushes both urban and rural households into poverty.…”
Section: Results and Discussion About Multidimensional Vulnerability ...mentioning
confidence: 99%
“…It is interesting to discover that routine physical examination is the primary determinant for household vulnerability to poverty in both urban and rural areas. Even in urban areas, more than 50% of households do not take a physical check-up on time, and empirical studies revealed that the early stages of several critical illness such as Hepaticsclerosis and cardiovascular disease are detected upon physical examination [80][81][82]. The deprivation of routine physical health examinations gives elders the risk of their minor ailments changing to major diseases, which can also offer a reasonable explanation as to why bad health is a key determinant that pushes both urban and rural households into poverty.…”
Section: Results and Discussion About Multidimensional Vulnerability ...mentioning
confidence: 99%
“…Anthropogenic disasters can be initiated by careless treatment of the working environment or poor organization of work or be purposefully carried out in the case of terrorist acts and civil conflicts with the aim of causing significant physical damage, loss of life or impact on the environment. Risk assessment [23] and optimum risk management is usually sought to reduce the consequences of such disasters. Risk assessment includes (1) hazard identification; (2) exposure assessment; (3) dose-response assessment and (4) risk characterization.…”
Section: Methodsmentioning
confidence: 99%